Slovenska izseljenska društva v zahodnoevropskih državah med obema svetovnima vojnama - Drnovšek, Marjan (Dve domovini, 1996)
The author provides an overview of Slovene emigrant societies in Western European countries up to 1940. The article was written on the basis of newspapers, calendars and references in journalistic articles, scientific mongraphs and papers.
Keywords: 1914-1940; izseljeniška društva; slovenski izseljenci; Zahodna Evropa